A two-year wastewater-based surveillance of SARS-CoV-2 trends within the Tshwane region, South Africa - Miss Gugulethu Dhlamini; Doctor David-Noel Nogbou; Doctor John Y Bolukaoto; Miss Prudence F Ndzinisa; Proffesor Maphoshane Nchabeleng; Doctor Andrew M Musyoki (International Journal of Infectious Diseases)
Introduction: Wastewater-Based epidemiology uses biological and chemical indicators for detection of infectious pathogens. This surveillance strategy forecast information on the presence, distribution, or the resurgence of diseases in countries with centralize sewage infrastructure. Would wastewater-Based SARS-CoV-2 surveillance offer an improved reflection of the community-level disease monitoring in country with limited resources settings? Method: A retrospective study design was used to investigate and compare SARS-CoV-2 detection levels and trends in 842 wastewater samples collected from ten wastewater treatment plants (WWTP) in Tshwane, South Africa, to levels reported in diagnostic samples from January 2021 to December 2022. The wastewater SARS-CoV-2 RNA was extracted using Qiagen RNA/DNA soil Kit and quantified by means of qRT-PCR targeting the neucleocapsid protein. Wastewater SARS-CoV-2 quantification analysis were performed using QuantiStudio Design & Analysis 2.7.0 software. Data on detection of COVID-19 from clinical samples was retrieved from the National Institute for Communicable Diseases (NICD) website. Wastewater SARS-CoV-2 viral load were compared to diagnostic data. Results: SARS-CoV-2 RNA was detected in 53% (451/842) of the ten WWTPs. In 2021, the highest wastewater SARS-CoV-2 viral load detected was of 42 882 copies/ml in June while the surge in clinical COVID-19 cases was reported by NICD with the highest incidence of 67 781 cases in July 2021. In August 2022 a SARS-CoV-2 viral load spike of 66 163 copies/ml was reported from wastewater while the NICD report 595 confirmed clinical COVID-19 cases within the same week. Discussion: Wastewater surveillance have enabled earlier detection of surge in clinical infection at community-level compared to diagnostic data. Street et al., 2021 and Jakariya et al., 2022 reported similar results in which wastewater surveillance demonstrate high sensitivity in early detection and monitoring of SARS-CoV-2 than diagnostic data. This current data showed that wastewater surveillance was able to give a better reflection of prevalence at community level even when fewer clinical cases were being reported. Conclusions: Wastewater-base epidemiology can serve as an effective complementary tool for the monitoring and predicting of diseases outbreak.